Las TIC’s como estrategia didáctica para el aprendizaje de Ciencias Naturales en los niños de sexto año de educación básica paralelo “A”, de la unidad educativa intercultural bilingüe “Monseñor Leonidas Proaño”, provincia de Chimborazo, cantón Riobamba, año lectivo 2015 - 2016 - Medina Medina, Christopher Mauricio (2017)
The objective of this research is to determine if ICTs – Information and Communication Technologies, as didactic strategies help in the learning process of Natural Sciences in children corresponding to the sixth year of basic education. Class “A” at “Monseñor Leonidas Proaño” Bilingual Educational Institution from the province of Chimborazo, Riobamba Country, during the 2015 – 2016 Academic year. It was evident that very little knowledge was present in the students concerning ICTs, and even worse on the handling of these tools. Consequently, it was necessary to gather information according to the research topic that is presented in the theoretical framework. The study method was the inductive – deductive, and quantitative since it handled statistical data from the observation sheet. It was applied, documentary, and field. The study population that was taken into account was composed of 28 children of sixth year of basic education at Monseñor Leonidas Proaño Elementary, and the technique utilized was the observation. Subsequently, the analysis and interpretation of the results obtained were carried out. The findings showed positive outcomes since they verified that the application on ITC’s as a didactic strategy helped to improve the learning of Natural Sciences in the children, thus achieving the objectives set. As a result, it was concluded that the introduction of ICTs in Natural Sciences significantly improves students learning processes by allowing them to have a better understanding of the contents presented in class, thus improving the cognitive capacities of the children.